ICDWiz: Visualizing ICD-11 Using 3D Force-Directed Graph - Jarernsri Mitrpanont (2022)
WHO released ICD-11 in 2018 and will be used in 2022. ICD-11 has been changed drastically in its complex structure, enormous size, multi-source of classifications and terminologies, and code of diseases multiplication. The transition from ICD-10 to ICD-11 will be extremely intricate and long process, especially for the international members. In this paper, we present the 3D visualization part of the ICDWiz system to uncover the ICD-11 using our modified 3D Force Directed Graph to visual the information and relationship of the multi-knowledge sources biomedical Concept-terms-strings-atoms or phrases. The Visualization construction and functions such as Initial graph, Collapsed Function, Ring Notation and Constructed Text Label are described. The testing is elaborated using the ICDWiz database which is developed based on UMLS-Metathesaurus structure. The result reveals the complex visual of the ICD-11 medical information such as diseases, symptoms and relationship integrated from multi-medical classifications such as ICD-11, ICD-10, ICD-10 TM (Thai Modification), MeSH, and SNOMED-CT. The mapping between ICD-10 and 11 is also visualized as well.